Arid Zone fruits research in India - PAREEK, O P (The Indian Journal of Agricultural Sciences, 2013)
In arid zone fruits better plant types have been selected form rich diversity in India, viz 'NB 5' and 'NB 9' in bael[Aegle marmelos (L.)Corr. Serr.];'Early Umran'in jujube (Ziziphus mauritiana Lam.);'Arka Sahan','Balangar','Mammoth' and 'RedSitaphal' in custard apple (Annona sayamosa L.);'Kachchh Selections in date palm (Phoenix daclylifera L.);'Krishna',Kanchan',NA 7",'GA 1'etc in emblic myrobalan or aonla (Emblica officinalis Gaertn.);'Excell','Deanna'and 'Conadria' in fig (ficus carica L.);'G 137','P 26',' GKVK 1' etc in pomegranate (Punica granatum L.); and 'Yogeshwar','PKM I','T 3'.'T 13 ' etc in tamarind (Tamarindus indica L.). Recommended cultivars of arid zone fruits are 'Varanasi' and 'Gorakhpur' of bacl; 'Gola','Seb', 'Early Umran' 'Mundia', 'Banarasi Karaka'and 'Kaithali' (mid-season), and 'Umran' (late) Of jujube; 'Halawy', 'Barhee', 'Shamran' of date plam; 'Banarasi,'Chakaiya', and 'Francis' of aonla; 'Poona', 'BlaCk Ischia' and 'Brown Turkey' of fig; 'Ganesh', 'Muskat', 'BasseinSeedless' and' Jalore Seedless] of pomegranate. A number of technologies of suitable cutivars or types, propagation andcultural practices, plant-protection measures and utilization methods have been developed. Projections for future researchin arid zone fruits are also given.